Evaluation of genetic variation among wild rice populations in Cambodia - Orn, Chhourn (Breeding science, 2015)
A total of 448 samples in five natural populations of wild rice (Oryza rufipogon) were collected in Cambodia. They were examined using 12 SSR and two chloroplast markers to evaluate the degree of variation among populations and the genetic structure within populations. In the two annual populations, the number of plants with homozygous alleles at all 12 SSR loci were high (66.3% and 79.5%), suggesting that these plants propagate mainly through self-pollination. In the three perennial populations, no individuals had all homozygous genotypes, but redundant genotypes resulted from clonal propagation were observed. Percentages of the redundant genotypes were highly varied (3.6%, 29.2% and 86.0%). This may be due to the different stable levels of environmental conditions. As for chloroplast genome, most of the wild plants showed the same chloroplast types as most Indica-type cultivars have. However, plants with different chloroplast types were maintained, even in the same population. In tropical Asian countries, many wild rice populations were observed under similar ecological conditions examined in this study. Therefore, the present results concerning population structure will be important to further elucidate genetic features of wild rice, and will also give strong clues to utilize and conserve wild natural genetic resources